Circular RNA MYLK as a prognostic biomarker in patients with cancers: A systematic review and meta‐analysis. Issue 9 (14th June 2022) - Foroumadi, Roham; Rashedi, Sina; Asgarian, Sara; Mardani, Mahta; Keykhaei, Mohammad; Farrokhpour, Hossein; Javanshir, Salar; Sarallah, Rojin; Rezaei, Nima
Abstract: Background: Circular RNA (circRNA) myosin light chain kinase (circMYLK) has recently received increasing attention in cancer biology. Several studies have suggested that circMYLK expression is linked to prognosis and clinicopathological characteristics of various malignancies. Aims: This study was carried out to systematically review the impact of circMYLK on the progression of multiple cancers and assess the significance of circMYLK in the prognosis and clinicopathological features of the patients. Methods: PubMed, Web of Science, and Embase were systematically searched until July 2, 2021. For qualitative synthesis, the signaling pathways of circMYLK in the progression of different cancers were summarized. Regarding the meta‐analysis, overall survival (OS) and eight clinicopathological characteristics of patients with cancers were addressed. Odds ratios (ORs) and hazard ratios (HRs) were calculated to assess the association of circMYLK with prognostic and clinicopathological features. Results: Twelve studies investigating the role of circMYLK in cancer progression met the inclusion criteria. Among these, seven studies investigated the prognostic significance of circMYLK, and nine studies ascertained the clinicopathological importance of circMYLK in patients with various malignancies. CircMYLK acts as a tumor promoter circRNA, leading to migration, proliferation, invasion, and metastasis of neoplastic cells and inhibiting their apoptosis through interaction with several miRNAs and corresponding downstream signaling pathways. Overexpression of circMYLK was correlated with poor OS (HR = 1.75; 95% confidence interval [CI] 1.52–2.02) and larger tumor size (OR = 2.90; 95% CI 1.03–8.15), higher T stage (OR = 2.49; 95% CI 1.20–5.18), lymph node metastasis (OR = 2.55; 95% CI 1.41–4.62), and higher TNM stage (OR = 4.62; 95% CI 2.99–7.14). Conclusions: CircMYLK is involved in the progression of numerous cancers via different signaling pathways. This circRNA can serve as a promising prognostic biomarker for several types of malignancies. Furthermore, high expression of circMYLK is associated with advanced clinicopathological characteristics in various tumors.